FROM THE EDITOR = Redaksioneel - Lategan, Bernard C. (Scriptura, 1984)
Interest in the literary aspects of the Bible and the accompanying hermeneutical issues is on the increase - as can be seen from this edition of Scriptura. The insights of modern literary theory are studied by more and more exegetes in order to gain a better understanding of Biblical material. This year’s annual meeting of the New Testament Society of SA will be devoted to hermeneutical issues under the general theme: Reading a text. Source - receptor - setting. A special guest at the meeting will be Professor Norman Petersen, well-known for his seminal work in opening up literary criticism for New Testament critics. After the meeting, Professor Petersen will visit several South African universities.